Skin conditions in liver transplant recipients in a Singapore academic medical center: A retrospective cohort studyCapsule Summary - Bertrand ShengYang Lian, MBBS, MRCP (JAAD International, 2021)
Background: Liver transplant recipients are at lifelong risk of immunosuppression-related cutaneous complications, such as malignancy and infection. Objective: Our study aims to assess the epidemiology of dermatologic conditions among liver transplant recipients in an academic medical center in Singapore. Methods: Medical records of liver transplant recipients on follow-up with gastroenterology and dermatology departments at the Singapore General Hospital between 2006 and 2021 were retrospectively reviewed. A literature review was subsequently performed on the keywords “liver transplant” and “dermatology.” Results: A total of 99 liver transplant recipients were identified in this study. Sixty-nine patients (70%) had at least 1 dermatologic condition. Inflammatory skin conditions were the most common (53%), followed by cutaneous infection (36%) and benign cutaneous tumors (30%). Malignant and premalignant lesions were the least common skin conditions reported (10%). Our study results concurred with many other studies reported worldwide, demonstrating a low cutaneous malignancy burden after liver transplantation. Limitations: The study included a small population size in a single center and did not have a pre-existing protocol for pretransplant dermatologic surveillance. Conclusion: Although the incidence of skin cancer after liver transplant in Singapore is low, the patients will benefit from long-term dermatology surveillance, given the long-term risks of infection and malignant skin conditions.